IMPLEMENTASI KEBIJAKAN PEMBENTUKAN SATGAS COVID-19 TINGKAT DESA DI DESA PUSEURJAYA KECAMATAN TELUKJAMBE TIMUR KABUPATEN KARAWANG - Liawati —; Hanny Purnamasari (Universitas Indo Global Mandiri, 2022)
This research is motivated by the problems contained in the Covid-19 Task Force at the village level, where the village is included in the sub-district with a fairly high level of Covid-19 cases in Karawang Regency. This study aims to identify how to implement the policy of establishing a Covid-19 task force at the village level, especially in Puseurjaya Village, Telukjambe Timur District, Karawang Regency. The method used in this research is a qualitative research method with a descriptive approach to describe the analysis of policy implementation indicators according to Gorge R. Edward III which can be measured through; (1) Communication, (2) Resources, (3) Disposition, and (4) Bureaucratic Structure through observation data collection techniques, in-depth interviews and documentation. The results showed that the implementation of the policy of establishing a village-level Covid-19 task force in eradicating the Covid-19 virus in Puseurjaya Village, Telukjambe Timur District, Karawang Regency has not been fully effective. This is evidenced by communication that has not been successful because the village government only made the Puseurjaya Village Covid-19 Task Force as many as 25 members but the task force did not work as it should, minimal human resources caused the Puseurjaya Village Covid-19 Task Force to be ineffective in eradicating the Covid-19 virus. and the Puseurjaya Village Covid-19 Task Force is no longer conducting outreach to the public regarding the prevention of the Covid-19 virus. The Covid-19 task force in this village has been declared vacuum starting from January 2021.Â Keywords: Covid-19, Policy Implementation, Village Government